(untitled) (Research, Society and Development, 2021)
Traditional knowledge about the use of medicinal plants leads an important socio-cultural practice in communities, as well as knowledge about potentially toxic species. Students of Youth and Adult Education (EJA - in brazilian initials) are characterized by having varied experiences, knowledge and cultural practices, which can contribute both to the recovery of traditional knowledge of communities and to the valorization of students’ previous knowledge, a fundamental characteristic within the precepts of EJA. Thus, the objective of this work was to rescue the knowledge of students of Youth and Adult Education about medicinal and toxic plants, comparing them with the existing scientific knowledge and stimulating the valorization of the knowledge from personal experiences. A qualitative and quantitative approach was used, based on a case study with the totality of EJA students from a municipal school. It was possible to observe that the popular knowledge of the students was in agreement with the scientific knowledge. In addition to contributing to the rescue of this knowledge, the students showed enthusiasm for socializing their knowledge and felt valued when realizing that their knowledge was in accordance with scientific information.